AGAINST MORAL HEDGING. (23rd July 2015) - Nissan-Rozen, Ittay
Abstract: It has been argued by several philosophers that a morally motivated rational agent who has to make decisions under conditions of moral uncertainty ought to maximize expected moral value in his choices, where the expectation is calculated relative to the agent's moral uncertainty. I present a counter-example to this thesis and to a larger family of decision rules for choice under conditions of moral uncertainty. Based on this counter-example, I argue against the thesis and suggest a reason for its failure – that it is based on the false assumption that inter-theoretical comparisons of moral value are meaningful.